The machine of power: the dystopian world in Death in the shell by Agop Melkonyan and The squares of the city by John Brunner (Colloquia Comparativa Litterarum, 2025)
The current text’s purpose is to compare the two novels mentioned in the article’s title, so it could examine some differences and some similarities in creating a fictional world, while emphasizing on the political dimensions of a dystopian narrative. The machine of power is a metaphor used in both novels, which are also comparable in their intention to show general mechanisms that take place within similar political regimes.
Keywords: dystopia; mechanisms of power; science fiction novel; Agop Melkonyan; John Brunner